2017
DOI: 10.1139/cjas-2016-0087
|View full text |Cite
|
Sign up to set email alerts
|

Carcass traits and meat fatty acid composition in Mediterranean light lambs

Abstract: Lamb meat is an important source of different fatty acids with numerous health benefits for the consumer. The aim of this study was to characterize carcass and meat traits in 14 Lacaune, 77 Ripollesa, and 33 Lacaune × Ripollesa pascual-type lambs (carcass weight, 13-16 kg) by using ultrasound and direct measurements on carcasses and laboratory analyses on meat samples. More specifically, ultrasound images and direct carcass measurements of the Longissimus dorsi (LD) were taken between the 12th and 13th ribs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…No significant differences were found between experimental treatments on average feed intake (810 ± 41.1 g/d), average daily body weight gain (328 ± 29.0 g/d), or body weight at slaughter (25.4 ± 2.13 kg). The IMF content (2.2 ± 0.97%) was within the common range previously reported for Mediterranean light lambs reared indoors on concentrate-based diets [ 23 , 24 ]. It should be noted that the Bligh and Dyer method used to extract the IMF may underestimate meat total lipid content [ 25 ].…”
Section: Resultssupporting
confidence: 84%
“…No significant differences were found between experimental treatments on average feed intake (810 ± 41.1 g/d), average daily body weight gain (328 ± 29.0 g/d), or body weight at slaughter (25.4 ± 2.13 kg). The IMF content (2.2 ± 0.97%) was within the common range previously reported for Mediterranean light lambs reared indoors on concentrate-based diets [ 23 , 24 ]. It should be noted that the Bligh and Dyer method used to extract the IMF may underestimate meat total lipid content [ 25 ].…”
Section: Resultssupporting
confidence: 84%
“…The fatty acid composition of the meat waste (Table 2) revealed the dominance of unsaturated fatty acids (53.36 ±0.33) over saturated fatty acids (46.64 ±0.19). Since the existing literature provides no data on the fatty acid content in butcher waste, a bibliographic review of the studies reporting the fatty acid content in different animal meats and fats was conducted [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. The review revealed that the fatty acid content varies greatly depending on whether the sample is flesh or lard and also on the origin of the sample (beef, lamb, rabbit, chicken, etc.).…”
Section: Characteristics Of the Meat Wastementioning
confidence: 99%